The method of selecting adaptive devices for the needs of drivers with disabilities - Stasiak-Cieślak Beata; Grabarek Iwona (Open Engineering, 2022)
This article presents the research which resulted in the creation of the method of automatic selection of adaptive devices for the needs of drivers with motor disabilities – ASA System. An expert system was used to build the method, which used databases from various fields of knowledge in the inference process. The databases were created on the basis of an analysis of the literature on the mobility of people with disabilities, a review of the operation of companies specializing in adaptations, verification of adaptive devices in terms of their functions, as well as various categories of disability. The knowledge of the individual selection of adaptive devices and expertize in this area made for specific recipients were used. Based on the accumulated knowledge, a simplified division of adaptive devices and classification of disabilities were implemented. The conclusions from analyses made it possible to formulate the rules necessary for the application process. A comparative analysis of the degree of consistency between the selection of devices generated by the ASA System (automatically) and the selection made by three experts (individually) for 44 people with various motor disabilities, was carried out. The results obtained confirmed usefulness of the expert system in building the method of automatic selection of adaptive devices, as well as the rightness of automating this process, due to the objectivity of the proposed method in comparison with individual, subjective selection carried out by experts.